IMPROVEMENT OF FOREIGN LANGUAGE EDUCATION OF FUTURE PROFESSIONALS FOR IMPROVING THEIR COMPETITIVENESS IN CONDITIONS OF GLOBALIZATION - Korotkova, Yuliya (Continuing Professional Education: Theory and Practice, 2019)
The article analyzes the problem of improving foreign language communicative competence of students of higher educational institutions as the condition to improve their competitiveness in the employment market. To the ways of improving foreign language communicative competence we include: cooperation between teachers of both a practical course of foreign language and of other disciplines (we consider the lack of interdisciplinary communication between such modules as «Listening», «Home reading», «Practice of oral and written speech», also insufficient is cooperation among teachers of foreign language and special disciplines); systematic scientifically-based use of ICT technologies in the educational process using the language (communication in a foreign language with students from other universities via e-mail, Forum, Skype, Net Meeting, holding of joint conferences, videoconferences, round tables, implementation of joint projects; functioning of Virtual learning environments in each higher educational institution; the gradual establishment of the online database of educational material; the establishment of multimedia laboratories, compulsory creating and functioning of language laboratories; the promotion of scientific and pedagogical workers to the creative use of ICTs); activation of academic mobility of students (their constant informing and encouraging to participate in such programs); the establishment of a public certification body of knowledge of foreign languages, whose branches would act in every region of Ukraine and provide an opportunity for Ukrainians not only to pass the exam and receive the certificate on proficiency in a certain foreign language, but the desire to receive appropriate training; improvement of theoretic-methodological principles of compiling curricula, textbooks, manuals, language.